The Role of Opinion Leaders in the Acculturation of the Togutil Tribe in East Halmahera Regency, North Maluku Province - HASAN, Bahrudin; SIHABUDIN, Ahmad; JAMALULLAIL, Jamalullail (PT Keberlanjutan Strategis Indonesia, 2021)
One of the 21 tribal groups in North Maluku, the Togutil Tribe still closely upholds its traditional beliefs and practices. They also form their own community and restrict interaction and communication with other ethnic groups, such as the Maba tribe. This study aimed to determine how opinion leaders' role in the acculturation between the Togutil tribe and the Maba tribe caused acculturation in East Halmahera Regency. The research approach used is qualitative research, which seeks to understand, explain and analyze the acculturation process between the Togutil tribe and other ethnic communities in the